Re-Injection of Formation Water and Sea Water to Increase Oil Recovery from Sandstone Rocks: A Laboratory Experiment Under Room Conditions - Naser, Madi; Omar Ibrahim Azouza; Khairi Ahmed R Masaud (Journal of Pure & Applied Sciences, 2022)
Laboratory tests and field applications show that low-salinity water flooding could lead to significant reduction of residual oil saturation. There has been a growing interest with increasing number of low-salinity water flooding studies. However, there are few quantitative studies on the effect of using sea-water injections on oil recovery. As oil production continues, a drop-in reservoir pressure will occur due to the loss of reservoir fluids, and this drop-in pressure will lead to a decrease in oil production. The reservoir pressure is maintained by the water injection process. Where sea-water is injected into the aquifer area below the oil area to support the tank pressure. This study presents a laboratory investigation of the effect of salinity injection water on oil recovery, permeability, and relative permeability in the water flooding process. This study was conducted using several samples of sandstone saturated with oil by placing them in the reservoir conditions by placing them in a vacuum oven to ensure complete saturation of the samples with oil and then extracting the oil from them using liquid permeability where the samples are injected. With the formation water until reaching the recovery plateau and obtaining an average reading, the flow, permeability and pressure difference are measured, as well as the relative permeability and recovery factor, then the samples are injected again with sea water and the new results are recorded through seawater injection. The results of this study showed an increase in oil recovery with decrease in residual oil saturation and increase in the recovery factor.